Avaliação ultrassonográfica quantitativa e qualitativa do canal do carpo em equinos - Evangelista, Felipe Carvalho [UNESP] (2013)
The carpal tunnel was sonographically evaluated in 60 quarter horse healthy equines in different age groups, divided into three groups, being these foals, young adults and adults, with 10 males and 10 females in each group. The aim of this study was the characterization and standardization of the structures of the carpal tunnel, through the ultrasound B-mode and the Doppler ultrasonography. Within the carpal tunnel were evaluated superficial digital flexor tendon and deep with the radial carpal flexor tendon. For each tendon was measured the height dimensions dorsal palmar, the medial lateral width and the area of the tendons. Besides the tendons were evaluated the medial palmar nerves and the lateral palmar according to the normal morphology and dorsal palmar dimension. In the Doppler ultrasound were standardized the Dopplerfluxometry indices of the radial arteries and palmar branch of the median artery. For the echogenicity and echotexture standardization of the tendons were performed the histogram. The mean area of the TSDF ranged from 99.20 to 123.20 mm2, of the TDDF from 114.60 to 143.80 mm2 and of the TFCR from 17.50 to 24.22 mm2. The mean diameter of the flexor retinaculum ranged from 1.33 to 1.55 mm, of the lateral palmar nerve from 0.93 to 1.09 mm, of the medial nerve palmar from 1.10 to 1.44 mm, of the artery radial from 2.54 to 3.06 mm and of the medial palmar artery from 4.23 to 5.47. The mean of the resistivity and pulsatility indexes of the radial artery ranged from 0.82 to 0.88 and from 2.02 to 3.73, respectively. The mean resistivity and pulsatility indexes of the medial palmar artery ranged from 0.72 to 0.84 and from 1.71 to 2.73, respectively. The mean resistivity and pulsatility indexes of the medial palmar artery ranged from 0.72 to 0.84 and from 1.71 to 2.73. In this study was concluded that there was no difference between the right and left limbs for the same animal and there is ...